2019
DOI: 10.1042/bsr20182370
|View full text |Cite
|
Sign up to set email alerts
|

MiR-19a as a prognostic indicator for cancer patients: a meta-analysis

Abstract: MiR-19a was aberrantly expressed in various types of cancers and was observed to be potentially associated with the prognosis of cancer patients. The present analysis aims to elucidate its precise predictive value in various human malignancies. Online electronic searches of PubMed, Web of Science (WOS), Embase in English and VIP, Wanfang, SinoMed, and the China National Knowledge Infrastructure (CNKI) in Chinese up to September 8, 2018 were conducted. As a result, in overall analysis, a significant association… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…Jiang et al identified that the miR-19b-3p significantly upregulated and led to colon cancer progression in 211 colon samples [79]. Similarly, overexpression of miR-19a was linked to a poor prognosis in various human cancers, including ESCC [80]. Our results revealed that the predicted HmiRT10 could be used as independent predictive biomarkers for the appropriate identification and treatment of ESCC.…”
Section: Discussionmentioning
confidence: 54%
“…Jiang et al identified that the miR-19b-3p significantly upregulated and led to colon cancer progression in 211 colon samples [79]. Similarly, overexpression of miR-19a was linked to a poor prognosis in various human cancers, including ESCC [80]. Our results revealed that the predicted HmiRT10 could be used as independent predictive biomarkers for the appropriate identification and treatment of ESCC.…”
Section: Discussionmentioning
confidence: 54%
“…37 Overexpression of miR-19a is a risk factor for poor prog- Article nosis in osteosarcoma, and is linked to the metastatic potential of the lymph nodes. 38 Moreover, overexpression of miR-19a contributes to chemoresistance in ovarian cancer and non-small cell lung cancers. 39,40 However, the role of miR-19a in CRC is controversial.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study by Hu et al, miR-19a-3p was identified as one of the most significantly upregulated miRNAs in hepatocellular carcinoma cells cultured under hypoxic conditions [ 21 ]. Upregulation of miR-19a has been analyzed as an independent risk of poor prognosis in multiple human malignancies [ 22 ]. In agreement with this, miR-19a has been found to be upregulated and play oncogenic roles in several cancers [ 23 , 24 ], including CRC [ 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%